2015
DOI: 10.1016/j.jmb.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modulation of Human Podocyte Vitamin D Receptor in HIV Milieu

Abstract: HIV has been reported to induce podocyte injury through down regulation of vitamin D receptor (VDR) and activation of renin angiotensin system (RAS); however, the involved mechanism is not clear. Since HIV has been reported to modulate gene expression via epigenetic phenomena, we asked whether epigenetic factors are contributing to down regulation of VDR. Kidney cells in HIV transgenic mice as well as HIV-infected podocytes (HIV/HPs) displayed enhanced expression of SNAIL, a repressor of VDR. To elucidate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 62 publications
(80 reference statements)
1
24
0
Order By: Relevance
“…We and other investigators have previously reported down regulation of podocyte VDR expression in adverse milieus both in vitro and in vivo studies (8, 9, 25, 26, 34). We asked whether high glucose milieu would also down regulate SIRT1 and enhance podocyte p53 expression and associated downstream signals.…”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…We and other investigators have previously reported down regulation of podocyte VDR expression in adverse milieus both in vitro and in vivo studies (8, 9, 25, 26, 34). We asked whether high glucose milieu would also down regulate SIRT1 and enhance podocyte p53 expression and associated downstream signals.…”
Section: Resultsmentioning
confidence: 55%
“…Recently, high Ang II states including high glucose and HIV milieus have been reported to cause down regulation of VDR in podocytes (8, 9, 25, 26, 34). High Ang II states down regulate podocyte VDR by multiple mechanisms including enhanced VDR degradation via proteasomal pathway and through transcription of CYP24A via de-repression of co-repressor complexes at CYP24A1 promoter (26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations